Constructing a framework for Return to Sport in elite football (PhD Academy Award) - Taberner, M. (British Journal of Sports Medicine, 2020)
The primary aim of my research was to construct a conceptual framework for on-pitch rehabilitation to help guide practitioners in the Return to Sport (RTS) process following injury in elite football. I then described how the framework was used to support RTS following; a common injury (hamstring strain), a rare injury (traumatic fracture) and a severe injury (anterior cruciate ligament reconstruction (ACLR)). Injury and re-injury are major problems in elite football. Inadequate rehabilitation is a risk factor for re-injury and football clubs strive to continually improve rehabilitation and RTS of injured players. The absence of specific frameworks to guide the on-pitch rehabilitation process was a surprising gap in the contemporary sports science literature